Answer:
k = 1,423x10⁵
Explanation:
For the reaction:
Fe₂O₃(s) + 3CO (g) ⇌ 2Fe(s) + 3CO₂(g)
You can obtain equilibrium constant, k, using:
ΔG° = -RT lnK (1)
ΔG° of the reaction is:
ΔGf° products - ΔGf° reactants, that means:
ΔG° = 2∆Gfº Fe(s) + 3∆Gfº CO₂(g) - (∆Gfº Fe₂O₃(s) + 3∆Gfº CO (g)
ΔG° = 2×0 + 3×-394,4kJ/mol - (-742,2kJ/mol + 3×-137,2kJ/mol)
ΔG° = -29,4 kJ/mol
Replacing in (1) knowing R = 8,314472x10⁻³ kJ/molK; T = 298K
-29,4 kJ/mol = -8,314472x10⁻³ kJ/molK 298K lnK
11,866 = lnK
1,423x10⁵ = k
I hope it helps!